Generation of highly reactive oxygen species on metal-supported MgO(100) thin films. Issue 36 (31st August 2016) - Song, Zhenjun; Fan, Jing; Shan, Yueyue; Ng, Alan Man Ching; Xu, Hu
Abstract : A series of highly reactive oxygen species are formed with the assistance of water on an insulating surface. Abstract : The formation of highly reactive oxygen species (ROS) on metal oxide surfaces has attracted considerable interest due to their diverse applications. In this work, we have performed density functional theory calculations to investigate the co-adsorption of oxygen and water on ultrathin MgO(100) films deposited on a Mo(100) substrate. We reveal that molecular oxygen can be completely decomposed stepwise with the assistance of water. Consequently, a series of highly ROS including superoxide, hydroperoxide, hydroxyl and single oxygen adatoms are formed on Mo(100) supported MgO(100) thin films. The reaction barriers accompanied by the generation of ROS are reported, and the influence of the thickness of MgO(100) films is also discussed. The promising routes to produce these species provide valuable information to understand the importance of synergy effects between the substrate, the co-adsorbed species, and the film thickness in multiphase catalyst design.